2020
DOI: 10.9734/ajee/2020/v12i130149
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Bioaccumulation in Periwinkle (Tympanotonus fuscatus) and Tilapia Fish (Oreochromis niloticus) Samples Harvested from a Perturbed Tropical Creek in the Niger Delta, Nigeria

Abstract: Different scientific studies with useful contributions in biomonitoring different environmental parameters and knowledge of their influences on aquatic ecosystem health and ultimately that of man have evolved through the years, however with scanty toxicological evidences. The present study was designed to investigate the concentrations of heavy metals in edible food of periwinkle and fish harvested from a perturbed creek in Niger Delta, Nigeria reported to constantly receive industrial effluent from two major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The swamp has been and is currently been impacted negatively as a consequence of several human activities within its vicinity which include farming and fishing activities, dumping of petrochemical wastes, accurring from the ODIGIE, O; OLOMUKORO, JO activities of the nearby Warri petroleum refinery and an upsurge in bunkering (crude oil theft) and illegal refining activities within the swamp and neighbouring creeks. Several authors have reported the suitablility and effectiveness of utilizing these representative benthic fauna and mudskipper as bio indicators with respect to aquatic niches exposed to varying levels of heavy metal pollution (Ikram et al, 2010;Chaiyaraa et al, 2013;Ansari et al, 2014;Abu and Nwokoma, 2016;Moslen et al, 2017;Aigberua and Izah, 2018;Numbere, 2019;Abiaobo et al, 2020). Earlier publications by Odigie and Olomukoro (2020a;2020b) profiled the heavy metal content of surface water and sediments collected from various sampled points within the perturbed Falcorp swamp and an adjoing creek; Ifie.…”
mentioning
confidence: 99%
“…The swamp has been and is currently been impacted negatively as a consequence of several human activities within its vicinity which include farming and fishing activities, dumping of petrochemical wastes, accurring from the ODIGIE, O; OLOMUKORO, JO activities of the nearby Warri petroleum refinery and an upsurge in bunkering (crude oil theft) and illegal refining activities within the swamp and neighbouring creeks. Several authors have reported the suitablility and effectiveness of utilizing these representative benthic fauna and mudskipper as bio indicators with respect to aquatic niches exposed to varying levels of heavy metal pollution (Ikram et al, 2010;Chaiyaraa et al, 2013;Ansari et al, 2014;Abu and Nwokoma, 2016;Moslen et al, 2017;Aigberua and Izah, 2018;Numbere, 2019;Abiaobo et al, 2020). Earlier publications by Odigie and Olomukoro (2020a;2020b) profiled the heavy metal content of surface water and sediments collected from various sampled points within the perturbed Falcorp swamp and an adjoing creek; Ifie.…”
mentioning
confidence: 99%